Associations between parental media mediation and youth attitudes about online privacy in a sample of US adolescents. (December 2022) - Corcoran, Erin; Shaffer, Emily; Warner, Morganne; Gabrielli, Joy
Abstract: Purpose: Youth engagement in privacy-related behaviors on social media associates with risks on- and off-line. Attitudes towards online privacy predict privacy-related behaviors. Media-specific parenting techniques may have the potential to impact youth attitudes about privacy, thus offsetting downstream risks. Methods: 1021 caregiver and youth ( M age  = 12.12; 42% female) dyads completed the TECH Parenting (Talk; Educate; Co-Use; House Rules) measure. Children reported on concern for privacy on social media. Parent and child report of TECH Parenting were regressed on privacy concern, controlling for covariates. Reporter discrepancy scores were calculated and regressed on privacy concern. Results: Youth concern for privacy online positively associated with Educate (parent and child report) and negatively associated with Talk (parent report) and Co-Use (child report). Reporter discrepancy in Talk also negatively associated with privacy concern. Conclusion: Mediation behaviors and discrepancy in parent/child report of mediation associated with youth privacy concern on social media. Findings elucidate an important area for future exploration to inform recommendations for parents around youth social media use and privacy concern. Highlights: Media-specific parenting behaviors may be an avenue by which to increase youth concern for privacy. Parent report of media mediation behaviors were higher across all domains than child report. Parent and child report of mediation behaviors differentially associated with youth privacy concern. Discrepancy between parent and child report associated with lower youth privacy concern.